Role of Nottingham Prognostic Index Scoring in Determining Prognosis of Breast Carcinoma in Different Age Groups - SHAHIDA NIAZI, RABIA BASHARAT, ABDULL, FARRUKH KAMAL (Journal of Fatima Jinnah Medical University, 2018)
The commonest malignancy among women is breast carcinoma world widely. It is the leading cause of death due to cancer among females in developing world but it remain second to lung carcinoma in developed world .The aim of this study is to determine the extent and spread of invasive breast carcinoma by applying Nottingham Prognostic Index (NPI) in patients of three different age groups for categorization into their respective prognostic groups thereby determining their morbidity and mortality.Out of total 140 mastectomy cases, 14 patients (10%) were under 35 years of age whereas 88 patients (62.85% ) were in age group between 35 to 50 years. 38 patients were over 50 years of age (27.14%).The tumor size ranged from 1cm to 10cm in largest dimension with average size of 5 cm. Out of the 140 cases, only one case (0.71%) was Grade-I, 126 (90%) were Grade-II, and 13 (9.2%) were Grade-III. Out of the 140 cases, 56(40%) cases showed no metastasis in axillary lymph nodes. In 32(22.8%) patients, 1-3 lymph nodes showed metastatic deposits. In 52(37.1%) patients, more than three lymph nodes were positive for metastasis. The largest number of lymph nodes received with mastectomy specimen was 16. NPI was applied to 140 cases. Out of total 140 cases, 75 cases (53.57%) were calculated as having prognostic index value between 3.5 and 5.4 and thus having moderate prognosis. Whereas 49 patients (35%) had Prognostic Index Value > 5.4 indicating Poor Prognosis. Only 16 patients (11.42%) had Prognostic Index less than 3.4 having Good Prognosis . It is concluded that it is very important to apply Nottingham Prognostic Index Scoring on Mastectomy Specimens of our patients to assess the prognosis and manage accordingly and also develop strategies to prevent it